Determinan Kepuasan Kerja dan Implikasinya Terhadap Komitmen Organisasi (Studi Pada Karyawan Biro Perjalanan Wisata di Kota Palembang) - Rini .; Heri Setiawan (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2016)
This study aims to determine the effect of leadership, motivation and organizational climate on job satisfaction and employee commitment. Sampling was done by proportionate random sampling. The sample in this study were employees of a travel agency as a member ASITA in South Sumatra consist of 185 people. The data were analyzed using multiple regression analysis using SPSS software for Windows version 19. The results showed that the leadership, motivation, organizational climate have significant effect on job satisfaction. There is no significant effect leadership on job satisfaction. There is no significant effect work motivation on job satisfaction. There is significant effect organizational climate on job satisfaction. There is significant effect leadership, motivation, organizational climate, job satisfaction on organizational commitment. There is significant effect leadership on organizational commitment. There is significant effect work motivation on organizational commitment. There is no significant effect organizational climate on organizational commitment. Based on the results of the studyÂ  manager of a travel agent should be increase level of employee satisfaction by providing better motivation, attention to the working environment more comfortable and conducive and awards both financially and non-financially so that employees are more committed to the company